Spolnost v času individualizma in racionalnosti - Bernik, Ivan (Družboslovne razprave, 2010)
Changes in sexual behaviour in contemporary Western societies have often been described as a new sexual revolution. Although accounts of this differ in many respects, they converge in asserting that the new sexual revolution has been related to the processes of the rapid individualisation, rationalisation and differentiation of sexual behaviour. Drawing on theories of occidental modernisation, the article claims that these processes have influenced the transformation of sexual behaviour much longer and in a less revolutionary way than assumed by the theorists of a new sexual revolution. This claim is also supported by surveys of sexual behaviour which show that most of the change in this field has been long-term and gradual. Given these claims, the idea of a new sexual revolution seems both theoretically and empirically unsubstantiated.
Keywords: sexual intercourse; Sexuality; Spolnost; Spolno vedenje; Sexual behavior; Modernizacija; Modernization; Individualism; Individualizem; Racionalnost; Rationality; družba; society; seksualna revolucija